Evaluation of health-related quality of life among transfusion dependent thalassemia major children aged 6-18 years - Maddireddy, Nadhvisal; Patil, Nivedita; Kamble, Priti; Kavthekar, Saiprasad; Agroya, Anjali; Anjan Prasad, Chittluru Nikhil (International Journal of Contemporary Pediatrics, 2025)
Background: Children with transfusion-dependent thalassemia major (TDTM) are vulnerable to issues in various aspects of psychological, physical, social, emotional, communication and educational which results in diminished health-related quality of life (HRQOL). Aim was to evaluate HRQOL and corelation with sociodemographic factors among TDTM children between the aged 6-18 years. Methods: This cross-sectional study involved 69 children with TDTM aged 6-18 years by using validated paediatric QOL inventory version 4.0 (Peds QL) to assess HRQOL, which includes four domains 1) physical functioning (8 items) 2) emotional functioning (5 items), 3) social functioning (5 items) and 4) school functioning (5 items) and were rated on a five-point Likert scale 0 to 4. The items on the Peds QoL were reverse scored and converted to a 0-100 scale. Higher scores signify better HRQOL. The data were analysed statistically. Results: The mean age of the cohort was 11.58±3.71 years while the majority were male (72.46%). Physical and school functioning scores were significantly lower in the 16-18 years group (p=0.0094) and (p=0.0413). There was no statistically significant difference in HRQOL between sexes. Educational status showed significantly higher total HRQOL scores in 7th 9th grade (p=0.0481). The frequency of blood transfusion did not significantly impact HRQOL. Deferasirox users reported higher total HRQOL scores. Conclusions: HRQOL was significantly impacted among TDTM children. Patients not receiving chelation therapy had recorded the lowest HRQOL scores, highlighting the importance of effective chelation in managing iron overload and improving HRQOL.